2018
DOI: 10.3390/molecules23092102
|View full text |Cite
|
Sign up to set email alerts
|

Improved l-Leucine Production in Corynebacterium glutamicum by Optimizing the Aminotransferases

Abstract: The production of branched-chain amino acids (BCAAs) is still challenging, therefore we rationally engineered Corynebacterium glutamicum FA-1 to increase the l-leucine production by optimizing the aminotransferases. Based on this, we investigated the effects of the native aminotransferases, i.e., branched-chain amino acid aminotransferase (BCAT; encoded by ilvE) and aspartate aminotransferase (AspB; encoded by aspB) on l-leucine production in C. glutamicum. The strain FA-1△ilvE still exhibited significant grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…This strain C. glutamicum MV-LeuF2 produced up to 181 mM L-leucine in the chemically defined medium along with precipitate of L-leucine after 72 h of the fed-batch fermentation [ 27 ]. Feng et al reported that a rational modification of aminotransferase activity improved L-leucine production through optimizing the aminotransferases [ 44 ]. L-leucine producing strain C. glutamicum WL-14, obtained by rational genetic engineering with mutant bacteria as the starting strain, exhibited the high L-leucine titer of 28.5 g L -1 [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…This strain C. glutamicum MV-LeuF2 produced up to 181 mM L-leucine in the chemically defined medium along with precipitate of L-leucine after 72 h of the fed-batch fermentation [ 27 ]. Feng et al reported that a rational modification of aminotransferase activity improved L-leucine production through optimizing the aminotransferases [ 44 ]. L-leucine producing strain C. glutamicum WL-14, obtained by rational genetic engineering with mutant bacteria as the starting strain, exhibited the high L-leucine titer of 28.5 g L -1 [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Strains used in this study are listed in This study Batch shake-ask fermentation was carried out in 500 mL shake ask with 50 mL of fermentation medium, and was referred to the methods described by Feng et al (2018). Inoculum was from a seed culture with ∆OD 562 =0.45-0.50 (at a dilution of 25-fold), and the inoculation amount was 10%.…”
Section: Strains Growth Medium and Culture Conditionsmentioning
confidence: 99%
“…before alaT and replacing native promoters of ilvBNC and leuA with the strong promoter P tuf improved l -leucine accumulation to 26.8 g/L [ 43 ]. To address the generation of by-products due to the substrate diversity of TA, the ilvE gene encoding TA was knocked out, and aspartate aminotransferase (AspB) was overexpressed in C. glutamicum FA-1 [ 63 ]. That strain produced 82.6% more l -leucine (20.8 g/L) than the original strain, while l -valine production remained unaltered, indicating that AspB has higher specificity for the precursor of l -leucine than l -valine production [ 63 ].…”
Section: Regulation Of Metabolic Flux Of Bcaas Production Pathwaysmentioning
confidence: 99%
“…In addition, the substrate diversity of AHAIR, DHAD, and TA should be determined via mutagenesis or by replacing them with their isozymes with substrate specificity to realize the production of individual BCAAs. For example, transaminase TyrB from E. coli , which catalyzes only 2-ketoisocaproate to produce l -leucine, could replace the substrate-diverse transaminase TA in C. glutamicum to allocate more carbon source for the sole production of l -leucine [ 63 ].…”
Section: Regulation Of Metabolic Flux Of Bcaas Production Pathwaysmentioning
confidence: 99%